A new approach for predicting gas chromatography retention indices of polycyclic aromatic sulfur heterocycles. Issue 5 (1st April 2019) - Moustafa, Nagy E.; Mahmoud, Kout El‐Kloub Fars
Abstract: Here we present a novel and simple approach for predicting retention indices of polycyclic aromatic sulfur heterocycles on (5%‐Phenyl)‐methylpolysiloxane stationary phase using a new set of structural descriptors based on substituent positions. The prediction method modeled correlations between retention indices and structural parameters for alkyl substituted benzothiophenes and dibenzothiophenes. Five models were created: two for uni‐ and di‐ substituted benzothiophenes homologous series, and three for the following non‐homologous series: (i) uni‐ to tri‐ substituted benzothiophenes; (ii) uni‐ to tetra‐substituted dibenzothiophenes and (iii) isomers of benzo[b]naphtha[2, 1‐d]thiophene and benzo[b]naphtha[1, 2‐d]thiophene. Retention was highly correlated with structural parameters, and all models had high correlation coefficients, low root mean‐squared errors, and low mean absolute percentage errors for the homologous series. For non‐homologous models, R‐values were 0.998 for dibenzothiophenes, 0.995 for benzothiophenes, and 0.991 for benzo[b]naphtha[2, 1‐d]thiophene and benzo[b]naphtha[1, 2‐d]thiophene, lower than for homologous series. Our approach represents a simple strategy for the prediction of experimental retention indices values without the need for state‐of‐the‐art technology.